2017
DOI: 10.1016/j.renene.2017.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of performance of wave turbine during stall using passive flow control: First and second law analysis

Abstract: Wells turbine is the most common type of self-rectifying air turbine employed by Oscillating Water Column (OWC) wave energy devices due to its technical simplicity, reliability, and design robustness. Because it subjected to early stall, there were many endeavors to improve the energy extraction performance of Wells turbine within the stall regime. Using the multi suction slots as a passive flow control can help obtaining a delayed stall. Two, three and four suction slots were investigated to improve the perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Nevertheless, in a large body of literature, entropy generation in the presence of turbulent flows is calculated considering only the contribution of the mean flow. This simplification has been adopted for Wells turbines [66,67,68,69,71], pipe flows [61,44], and turbine blades [51]. Herwig et al [34] demonstrated how neglecting the entropy produced by turbulent fluctuation may lead to errors in the global entropy production, as well as to misleading conclusions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, in a large body of literature, entropy generation in the presence of turbulent flows is calculated considering only the contribution of the mean flow. This simplification has been adopted for Wells turbines [66,67,68,69,71], pipe flows [61,44], and turbine blades [51]. Herwig et al [34] demonstrated how neglecting the entropy produced by turbulent fluctuation may lead to errors in the global entropy production, as well as to misleading conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…Wells turbines have been studied extensively, both experimentally [15,31,24,63,74,53,57,48] and numerically [40,62,17,76,30,72,32,27], but mainly from a first-law perspective. More recently, a number of authors [66,67,68,69,71] have focused on the irreversibilities in this component, trying to link the amount of available work (exergy) and the entropy produced.…”
mentioning
confidence: 99%
“…counter-clockwise in Wells turbines and clockwise in oscillating airfoils (this statement is actually incorrect [18]). The presence of dynamic effects in Wells turbine was the focus of the recent numerical investigations by [19][20][21][22][23][24], who gave essentially very similar explanations. In this short note, it will be demonstrated how these results are in contradiction with well established literature on rapidly moving airfoils and wings, and are likely to be caused by errors in the analysis of the experiments and in the setup of the numerical simulations.…”
Section: Introduction Wells Turbines and Owc Systemsmentioning
confidence: 88%
“…In light of the discrepancies outlined in Section II, the authors of this note have considered important to verify the numerical results presented in older studies, noticing how none of them [11][12][13][14][15][16][17][19][20][21][22][23][24] presented an accurate analysis of the numerical errors due to temporal discretization. This appeared curious to say the least, given the importance of excluding any phase errors [41][42][43] in a study that deals with hysteresis.…”
Section: Revisiting the Cause Of The Hysteresismentioning
confidence: 95%
“…Techniques were developed to manipulate the boundary layer, either to increase the lift or decrease the drag, they are classified under the general heading of boundary layer control or flow control [56,57]. Methods of flow control to achieve separation postponement, lift enhancement and drag reduction have been considered in these studies.…”
Section: Introductionmentioning
confidence: 99%